Influence of Supercritical Carbon Dioxide on the Activity and Conformational Changes of α-Amylase, Lipase, and Peroxidase in the Solid State Using White Wheat Flour as an Example - Milena Ivanović; Željko Knez; Maja Leitgeb (Foods, 2023)
Green technologies using renewable and alternative sources, including supercritical carbon dioxide (sc-CO2), are becoming a priority for researchers in a variety of fields, including the control of enzyme activity which, among other applications, is extremely important in the food industry. Namely, extending shelf life of e.g., flour could be reached by tuning the present enzymes activity. In this study, the effect of different sc-CO2 conditions such as temperature (35–50 °C), pressure (200 bar and 300 bar), and exposure time (1–6 h) on the inactivation and structural changes of α-amylase, lipase, and horseradish peroxidase (POD) from white wheat flour and native enzymes was investigated. The total protein (TPC) content and residual activities of the enzymes were determined by standard spectrophotometric methods, while the changes in the secondary structures of the enzymes were determined by circular dichroism spectrometry (CD). The present work is therefore concerned for the first time with the study of the stability and structural changes of the enzyme molecules dominant in white wheat flour under sc-CO2 conditions at different pressures and temperatures. In addition, the changes in aggregation or dissociation of the enzyme molecules were investigated based on the changes in particle size distribution and ζ-potential. The results of the activity assays showed a decrease in the activity of native POD and lipase under optimal exposure conditions (6 h and 50 °C; and 1 h and 50 °C) by 22% and 16%, respectively. In contrast, no significant changes were observed in α-amylase activity. Consequently, analysis of the CD spectra of POD and lipase confirmed a significant effect on secondary structure damage (changes in α-helix, β-sheet, and β-turn content), whereas the secondary structure of α-amylase retained its original configuration. Moreover, the changes in particle size distribution and ζ-potential showed a significant effect of sc-CO2 treatment on the aggregation and dissociation of the selected enzymes. The results of this study confirm that sc-CO2 technology can be effectively used as an environmentally friendly technology to control the activity of major flour enzymes by altering their structures.